The path to minimizing instability in developmental dysplasia of the hip: is Capsulorrhaphy a necessity or a futile habit? - Ramin Zargarbashi; Mohammadreza Bozorgmanesh; Behnam Panjavi; Fardis Vosoughi (BMC Musculoskeletal Disorders, 2021)
Abstract Background To evaluate and quantify the intraoperative effect of capsulorrhaphy on the deep seating of femoral head within the acetabulum as measured by medial joint space, a surrogate measure of acetabular-head contact. Methods In order to determine the exact effect of capsulorrhaphy, we prospectively scrutinized a consecutive sample of 18 patients with unilateral dysplastic hips aging > 18 months and followed them for a period of at least 12 months. The procedure of open reduction is described in detail. Two pediatric orthopedists carried out the operations from August 2014 to January 2019 at a tertiary pediatric hospital. Intraoperatively, AP radiographs of the pelvis were obtained before and after capsulorrhaphy. The distance between the inferomedial edge of the proximal femoral metaphysis and the lateral edge of the obturator foramen was recorded. To determine if there were differences in medial joint space due to capsulorrhaphy, a generalized linear model was run on the study sample. All patients were followed for at least 12 months to determine the rate of re-dislocation. Results Mean age (±standard deviation) of the participants was 37.5 (±24.7) months. All cases underwent Salter osteotomy, 5 cases needed femoral shortening (27.8%) and none needed derotational osteotomy. Capsulorrhaphy lead to a statistically significant decrease in the mean medial joint space from 1.59 cm before (95% CI: 1.12–2.05) to 0.76 cm after (95% CI: 0.50–1.02) the capsulorrhaphy (P < 0.001). When we took the effect of age into account the corresponding figures were 1.47 (95% CI: 1.22–1.75) and 0.67 (95% CI: 0.39–0.94), respectively (P < 0.001). After follow up periods of 1 to 5.5 years, none of the patients experienced instability or re-dislocation. Conclusions Capsulorrhaphy, independently, of age was associated with a 1-cm decrease in the mean medial hip joint space and a more deeply seated femoral head. Furthermore, this study presents a successful experience with capsulorrhaphy to prevent hip instability.